Heat rechperation in foundry furnaces - L. E. Rovin; A. V. Tkachenko; S. L. Rovin (Литьë и металлургия)
The article gives analysis of the operation efficiency of various foundry furnaces, in particular, the cupola and forging furnaces. It studies heat balances of the furnaces and possible application of secondary power resources (SPR) — exhaust gases heat. It gives evaluation of the cupola and heating furnace SPR exergy with study and presentation of the most rational variants of solutions providing for the SPR minimization.